EFFECT OF ADDITIONAL ROSELLA EXTRACT (Hibiscus sabdariffa) ON THE ORGANOLEPTIC QUALITY OF SHRIMP PASTE (Acetes sp) - Sulistiadi Sulistiadi; N.Ira Sari; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract This study aims to determine the effect of additional rosella extract on the organoleptic and quality of rebon shrimp paste during storage at room temperature. The research method used is to obtain a natural preservative formula that can be used for preserving rebon shrimp paste, increase the use value of flower plants such as rosella as a preservative or anti-bacterial in rebon shrimp paste, obtain preservatives that are safe for human health and become a reference for similar research, preservation effect can be developed. Based on the research, the addition of rosella extract P0(0%) P1(3%) P2(5%) and P3 (7%) in the processing of rebon shrimp paste had a significant effect on the texture and had no significant effect on the appearance and aroma value. The addition of rosella extract by 5% (50 mL) is the best treatment in terms of the organoleptic quality of the rebon shrimp paste which has a value of (7.82) with the criteria of having a brownish color and not pale, aroma value (7.41) has a distinctive smell of shrimp paste and does not sting the nose (not rancid), the texture value (7.99) is solid and not mushy..Keywords: rosella, shrimp paste, organoleptic